Functional and medicinal beverages - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Science of beverages, 2019)
Functional and Medicinal Beverages, Volume Eleven, in the Science of Beverages series, discusses one of the fastest growing sectors in the food industry. As the need for research and development increases based on consumer demand, the information in this volume is essential. This reference includes the latest research trends, nutritive and medicinal ingredients, and analytical techniques to identify health beneficial elements. The contents of the book will bring readers up-to-date on the field, thus making it useful for researchers and graduate students in various fields across the food sciences and technology. --